Emission Spectra for the Isotopic Molecule Lithium Hydride - Baghdad Science Journal (مجلة بغداد للعلوم)
A study of the emission spectra of isotopic for electronic states has been carried out. The energies of the vibration levels ( =0,1,..25) and the values of spectral lines R(J) and P(J) versus rotational quantum number (J=0,1..25). It was found that were an increase of the value of R(J) with the increase of the values of J was found while the value of P(J) decreases with decreasing of the values of J . It was found that corresponding to R(J) and P(J) the spectral line R(J) increases when the values of m increased.